2022
DOI: 10.1101/2022.07.12.499748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymmetric learning of dynamic spatial regularities in visual search: facilitation of anticipated target locations, no suppression of predictable distractor locations

Abstract: Static statistical regularities in the placement of targets and salient distractors within the search display can be learned and used to optimize attentional guidance. Whether statistical learning also extends to dynamic regularities governing the placement of targets and distractors on successive trials has been less investigated. Here, we applied the same dynamic cross-trial regularity (one-step shift of the critical item in clock-/counterclockwise direction) either to the target or a distractor, and additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 44 publications
3
13
1
Order By: Relevance
“…When the target was a bottom-up salient shape-singleton item (among differently but homogeneously shaped non-target items), summoning focal attention automatically, participants were able to extract the dynamic target-to-target location shift across trials, as evidenced by facilitated responding to targets at the new, predictable location (compared to targets at non-predictable, random locations). This is consistent with our own study (Yu et al 2023), in which the search target could also be detected and localized ‘in parallel’; we, too, found that search was facilitated when the target moved predictably across consecutive trials to the neighboring position in either clockwise or anticlockwise (blocked) direction – a somewhat simpler dynamic regularity compared to that introduced by Li and Theeuwes (2020). 1…”
Section: Why Would Dynamic Target-location Probability-cueing Be Depe...supporting
confidence: 92%
See 4 more Smart Citations
“…When the target was a bottom-up salient shape-singleton item (among differently but homogeneously shaped non-target items), summoning focal attention automatically, participants were able to extract the dynamic target-to-target location shift across trials, as evidenced by facilitated responding to targets at the new, predictable location (compared to targets at non-predictable, random locations). This is consistent with our own study (Yu et al 2023), in which the search target could also be detected and localized ‘in parallel’; we, too, found that search was facilitated when the target moved predictably across consecutive trials to the neighboring position in either clockwise or anticlockwise (blocked) direction – a somewhat simpler dynamic regularity compared to that introduced by Li and Theeuwes (2020). 1…”
Section: Why Would Dynamic Target-location Probability-cueing Be Depe...supporting
confidence: 92%
“…Chun and Jiang 1998), Giménez-Fernández et al (2020) found that many participants were actually aware of the target’s unequal ( static ) spatial distribution. In a recent study of dynamic target-location probability cueing in pop-out search (Yu et al 2023), we likewise found a substantial number of participants to be explicitly aware of the dynamic (cross-trial) target regularity, and we observed the dynamic target-location probability-cueing effect to be significant only in the group of aware participants.…”
Section: Why Would Dynamic Target-location Probability-cueing Be Depe...supporting
confidence: 58%
See 3 more Smart Citations